Three-Dimensional Ultra-Wideband Antenna: From Guiding Physical Considerations to Sequential Computer Optimization of Parameters and Characteristics - Victor P. Belichenko; Yuri Buyanov; George Dymov; Aleksandr Mironchev; Aleksandr Gorst (Applied Sciences)
Features of radiation from a three-dimensional ultra-wideband (UWB) unidirectional antenna are studied within the framework of the theory of characteristic modes. The antenna has a very simple structure and is distinguished by a rational use of accommodation volume. It has been found that a very wide matching band is provided by the simultaneous excitation of modes of two groups. Since the modes of each group have similar directional patterns, the stability of the antenna directional pattern also occurs practically within the entire matching band.